Analisis Pemanfaatan Media Pembelajaran IPA di SD - Dela Diana; Sukamti Sukamti; Sri Estu Winahyu; Dela Diana; Sukamti Sukamti (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The purpose of this research to determine the use of science learning media, types of learning media used, obstacles faced by teachers and efforts to deal with obstacles in the use of science learning media at SDN Polehan 5 Malang. This type of research is phenomenological research with a qualitative descriptive method. The subjects of this study were the first to sixth grade teachers. Data collection techniques used include observation, interviews, and documentation. The data analysis technique uses the data reduction stage, data presentation and conclusions. The results showed that (1) the types of science learning media used by the teacher were natural environment media, visual media, audio visual media, physical object media and multimedia media, (2) the use of science learning media at SDN Polehan 5 Malang was still low, four of six teachers still do not use science learning media when teaching, (3) the obstacles faced by teachers in the use of science learning media are the limited facilities owned by the school and the limited ability of the teacher, (4) the efforts made are to improve the teacher's ability by studying with colleagues work, attended training on the use of learning media from the Malang city office. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pemanfaatan media pembelajaran IPA, jenis media pembelajaran yang digunakan, kendala yang dihadapi guru serta upaya dalam menghadapi kendala dalam pemanfaatan media pembelajaran IPA di SDN Polehan 5 Malang. Jenis penelitian ini adalah penelitian fenomenologi dengan pendekatan kualitatif metode deskriptif. Subjek penelitian ini adalah guru kelas satu sampai kelas enam. Pengumpulan data dalam penelitian ini menggunakan teknik observasi, wawancara, dan dokumentasi. Teknik analisis data meliputi tiga tahap yaitu tahap reduksi data, penyajian data dan kesimpulan. Hasil penelitian menunjukkan bahwa (1) jenis media pembelajaran IPA yang digunakan guru adalah media lingkungan alam, media visual, media audio visual, media objek fisik dan media multimedia, (2) pemanfaatan media pembelajaran IPA di SDN Polehan 5 Malang masih rendah, empat dari enam guru masih belum menggunakan media pembelajaran IPA ketika mengajar, (3) kendala yang dihadapi guru dalam pemanfaatan media pembelajaran IPA yaitu keterbatasan fasilitas yang dimiliki sekolah dan keterbatasan kemampuan yang dimiliki guru, (4) upaya yang dilakukan adalah meningkatkan kemampuan guru dengan belajar bersama rekan kerja, mengikuti pelatihan penggunaan media pembelajaran dari dinas kota Malang.